Karakteristik Yakuwarigo dalam Tokoh Anime Gintama - Izzatul Maulina; Lisda Nurjaleka (KIRYOKU, 2020)
This study aims to analyze and categorize the type of yakuwarigo or role language on the Anime of Gintama. Role language, or known as Yakuwarigo in Japanese, is a set of language features associated with a particular type of character in the virtual world. The characteristic of these languages variation such as vocabulary, grammar, intonation, and accent patterns. (Kinsui, 2003). This study also investigates the function of these language variation types focusing on the yakuwarigo types in Anime Gintama. The data collection technique that was used is the note technique. The data analysis technique used in this study was the reading markah analysis technique followed by a descriptive qualitative data analysis technique to present the results of the data analysis. The results show that the type of Yakuwarigo found in Anime Gintama shows the variation of the character itself. Seven types of yakuwarigo seen from 10 Gintama anime characters, namely, aruyo kotoba, hakase go, onee kotoba, joseigo, danseigo, chara gobi, and Osaka ben. And the particular type of the yakuwarigo’s characteristics was shujoshi and specific types of expression used by these characters.